Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1103/physrevb.82.125429
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Raman spectra from single-, few-, and many-layer graphene with increasing disorder

Abstract: We report on the micro-Raman spectroscopy of monolayer, bilayer, trilayer, and many layers of graphene ͑graphite͒ bombarded by low-energy argon ions with different doses. The evolution of peak frequencies, intensities, linewidths, and areas of the main Raman bands of graphene is analyzed as function of the distance between defects and number of layers. We describe the disorder-induced frequency shifts and the increase in the linewidth of the Raman bands by means of a spatial-correlation model. Also, the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
444
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(483 citation statements)
references
References 38 publications
35
444
1
3
Order By: Relevance
“…(1) reduces to a single Lorentzian centered at ω(0). This Raman line-shape interpretation, which is known in literature as "phonon confinement model" or "spatial correlation model," has been successfully applied to explain the Raman scattering from several ion-bombarded crystals, for example, graphene [16], graphite [25], and GaAs [26], as well as to estimate the domain size of microcrystalline silicon [27,28] and the width of silicon nanowires [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) reduces to a single Lorentzian centered at ω(0). This Raman line-shape interpretation, which is known in literature as "phonon confinement model" or "spatial correlation model," has been successfully applied to explain the Raman scattering from several ion-bombarded crystals, for example, graphene [16], graphite [25], and GaAs [26], as well as to estimate the domain size of microcrystalline silicon [27,28] and the width of silicon nanowires [29].…”
Section: Resultsmentioning
confidence: 99%
“…It has indeed been reported that both Pos(E ) and Pos(A 1 ) decrease (increase) with tensile (compressive) in-plane strain [11,24], which is once again contrary to our experimental observations. However, although doping and strain will have an effect on the Raman spectra, the observed disorder-related evolution of the first-order peaks can instead be explained using a "phonon confinement model," as reported for ion-bombarded graphene [16] and other disordered crystals [25][26][27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of the samples presented two additional disorder induced vibrational modes. The D mode located at 1,330-1,350 which is an intervalley process, originating from the transverse optical phonons around the Brillouin zone boundary K (Martins Ferreira et al, 2010). The D + D' mode located at ∼2,900 cm −1 , which is a combination band of the D and the D' vibrations.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that this dependence has a quite general character with a maximum of the ratio (equal to about 3 in the case of 514 nm excitation) occurring at nD≈8×10 12 cm -1 . 23 The maximum value of I(D)/I(G) was obtained after the first (Ag) and the third (ZrO2) deposition, when the areal densities of the deposited material were 1.5×10 14 cm -1 and 2.7×10 15 , respectively. Consequently, only a small part of deposited atoms or ions -5% in the case of Ag and 0.3% in the case of ZrO2 -were active in forming the defects altering the Raman spectra.…”
Section: The Density Of the Induced Defects Nd Can Be Estimated From mentioning
confidence: 99%